Finding Out the Potency of Nusa Tenggara Timur in Poverty Allevation: The Effect of Local Government’s Policy - Matondang, Erlinda (Jurnal Bina Praja, 2017)
Poverty issue in Nusa Tenggara Timur (NTT) has happened for several years. Some efforts have been done, but there is no significant impact. Poverty issue in NTT is being the concern of Indonesia’s government not only because the high number of poorer, but also the location which is in border territory of Indonesia-Timor Leste. Actually, realized or not, NTT has great potencies behind the problem caused by its dry soil and some social issue in its society. Some of those potencies are able to be seen in five local economic sectors, i.e. demography, forestry, farming and animal husbandry, trading, and tourism. This article is written to explain how big potencies of NTT and how to manage it in order to alleviate poverty. The approach used in this article is qualitative approach with literature review as collecting data method. There is no special method used in analysing this article; it is just objective analysis based on current data, situation, and condition. Based on the analysis, there are so many potencies in NTT, but they have not been developed well, whereas people stuck in current situation, so there is no significant achievement in poverty alleviation efforts. Potency utilization can be optimally hold through strategic, effective, and efficient efforts supported by government, both national and local, and NTT society. Through potency optimization, poverty rate in NTT should be able to be push down.